CRISPR/Cas System: A Potential Technology for the Prevention and Control of COVID-19 and Emerging Infectious Diseases - Ding, Ronghua; Long, Jinzhao; Yuan, Mingzhu; Jin, Yuefei; Yang, Haiyan; Chen, Mengshi; Chen, Shuaiyin; Duan, Guangcai (Frontiers in Cellular and Infection Microbiology, 2021)
The continued global pandemic of coronavirus disease 2019 (COVID-19) poses a serious threat to global public health and social stability and it has become a serious global public health problem. Unfortunately, existing diagnostic and therapeutic approaches for the prevention and control of COVID-2019 have many shortcomings. In recent years, the emerging CRISPR/Cas technology can complement the problems of traditional methods. Biological tools based on CRISPR/Cas systems have been widely used in biomedicine. In particular, they are advantageous in pathogen diagnosis, clinical antiviral therapy, drug, and vaccine development. Therefore, CRISPR/Cas technology may have great potential for application in the prevention and control of COVID-19 and emerging infectious diseases in the future. This article summarizes the existing applications of CRISPR/Cas technology in infectious diseases with the aim of providing effective strategies for the prevention and control of SARS-CoV-2 and other emerging infectious diseases in the future.